2014
DOI: 10.4161/cbt.27821
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic acid antagonizes the hedgehog pathway by inducing patched

Abstract: Male germ cell tumors (GCTs) are a model for a curable solid tumor. GCTs can differentiate into mature teratomas. Embryonal carcinomas (ECs) represent the stem cell compartment of GCTs and are the malignant counterpart to embryonic stem (ES) cells. GCTs and EC cells are useful to investigate differentiation therapy and chemotherapy response. This study explored mechanistic interactions between all-trans-retinoic acid (RA), which induces differentiation of EC and ES cells, and the Hedgehog (Hh) pathway, a regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Benign HPV serotypes, not only high‐risk HPV, are implicated in Hh signal transduction. Oral retinoids was found to induce mRNA and protein expression of Patched 1, the Hh ligand receptor and negative regulator of this pathway (Busch et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benign HPV serotypes, not only high‐risk HPV, are implicated in Hh signal transduction. Oral retinoids was found to induce mRNA and protein expression of Patched 1, the Hh ligand receptor and negative regulator of this pathway (Busch et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…protein expression of Patched 1, the Hh ligand receptor and negative regulator of this pathway(Busch et al, 2014).Oral retinoids have shown an impressive therapeutic response in comparison and in addition to conventional therapies used for warts, with significant clinical response, extended remission time, and infrequent relapses. In a recent randomized trial to compare the efficacy of topical versus oral isotretinoin in the treatment of plane warts, 69% of patients in the low dose oral isotretinoin group (0.5 mg/kg/d) had complete remission, whereas 38% of patients in the topical isotretinoin group showed complete response(Kaur, Brar, Kumar, Brar, & Singh, 2017).…”
mentioning
confidence: 99%
“…The Hedgehog pathway is the primary focal point in Gorlin syndrome and experimental evidence highlights a significant intertwined relationship between the retinoic acid and Hedgehog pathways. Specifically, retinoic acid can antagonize the Hedgehog pathway by inducing Patched [ 30 ] and there are a number of reports demonstrating that the retinoic acid and Hedgehog pathways interact in developmental biology [ 31 ]. Retinoic acid deficiency, therefore, has the potential to eliminate a negative feedback process for the Hedgehog pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Due to severe adverse side-effects retinoic acid is not used to manage cancer in Gorlin syndrome patients and alternative retinoid pharmacons (e.g., Tazarotene) with significantly reduced toxicity show promise as alternative therapeutics [ 8 ]. Among the pleiotropic effects of retinoids, the regulation of stem cell differentiation has led to important applications in differentiation therapy [ 30 ]. It is noteworthy that short term (24 h) retinoic acid treatment in vitro can induce human stem cell differentiation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can heterodimerize and recognize specific retinoic acid response elements (RAREs) in genes promoter regions. It has been reported that RA-treatment increases PTCH1 expression, through homeobox transcription factor Myeloid Ecotropic Viral Integration Site [40], with consequent inhibition of SMO and repression of the Hh signaling pathway. Its target genes include GLI1, PTCH1, CCND1, and cyclin E. RA-mediated induction of PTCH1 did not depend on SMO since their inhibitors do not prevent the induction [40].…”
Section: Retinoidsmentioning
confidence: 99%